Hubungan status antropometri dan kebiasaan olahraga dengan kadar gula darah pada pasien diabetes melitus tipe 2 di RSUD Dr. Moewardi - Mega Safinaz, Cindy Luthfian Ayu; Mushlihoh, Arwin; Kusumawati, Dewi (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) is a metabolic syndrome disease characterized by high blood sugar levels influenced by obesity and physical inactivity.  Body mass index (BMI), waist circumference, waist-to-height ratio (WtHR) and neck circumference are proven to detect central obesity. Good exercise habits can control blood sugar levels.Objective: to determine the assosiation between anthropometric status (BMI, waist circumference, WtHR, neck circumference) and exercise habits with blood sugar levels in T2DM patients.Methods: This study is a quantitative observational study with a cross sectional design in 102 T2DM patients  internal medicine polyclinic at Dr. Moewardi Hospital through purposive sampling. Anthropometric status data were collected by direct measurement, exercise habits were measured using Baecke's exercise habits questionnaire, and blood sugar level data were obtained from patient medical records. The correlation test used the spearman test with a 95% confidence level. Multivariate test using multiple linear regression.Results: There was no assosiation between BMI, neck circumference and fasting blood sugar levels ( p=0,153; p=0,179). There is a significant assosiation between waist circumference, WtHR, exercise habits with fasting blood sugar levels (p=0,004; p=0,003; p=0,000). Waist circumference, WtHR and exercise habits have a significant effect on fasting blood sugar levels (p=0,001).Conclusion: There is a significant assosiation between waist circumference, WtHR and exercise habits on fasting blood sugar levels, while BMI is not significant.